2017
DOI: 10.1177/0886260517696871
|View full text |Cite
|
Sign up to set email alerts
|

Stalking Victimization in LGBTQ Adults: A Brief Report

Abstract: Stalking is often considered to be a form of interpersonal violence; yet, despite an increase in lesbian, gay, bisexual, transgender, and queer (LGBTQ)-specific research on other forms of interpersonal violence, such as intimate partner violence and sexual assault, there is a relative lack of literature on stalking victimization of LGBTQ individuals, particularly as it relates to gender identity. This is problematic given the results of numerous studies indicating LGBTQ individuals, and transgender individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…The current research shows that SV, stalking, and IPV continue to be significant public health issues and that not all groups experience these types of violence equally. These findings are consistent with previous research, albeit some based on localized data, that LGB individuals experience a higher prevalence of various forms of violence compared with heterosexual individuals (Armstrong et al, 2018; Edwards et al, 2015; Goldberg & Meyers, 2013; Langenderfer-Magruder et al, 2017; Walters et al, 2013; Waters, Jindasurat, & Wolfe, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current research shows that SV, stalking, and IPV continue to be significant public health issues and that not all groups experience these types of violence equally. These findings are consistent with previous research, albeit some based on localized data, that LGB individuals experience a higher prevalence of various forms of violence compared with heterosexual individuals (Armstrong et al, 2018; Edwards et al, 2015; Goldberg & Meyers, 2013; Langenderfer-Magruder et al, 2017; Walters et al, 2013; Waters, Jindasurat, & Wolfe, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In a recent college sample (data collected from eight New England universities), 53.1% of sexual minority students experienced unwanted pursuit compared with 36.0% of heterosexual students (Edwards et al, 2015). Langenderfer-Magruder, Walls, Whitfield, Kattari, and Ramos (2017) analyzed data collected from an anonymous group of adults in Colorado and found that transgender, bisexual, and queer individuals had the highest prevalence of lifetime stalking victimization.…”
mentioning
confidence: 99%
“…Across eight U.S. educational institutions, 53.1% of sexual minority students experienced unwanted pursuit, significantly higher than the heterosexual participants (36.0%; Edwards et al, 2015). Transgender, bisexual, and queer individuals had the highest prevalence of lifetime stalking victimization in a large community-based sample ( N = 1,116; Langenderfer-Magruder et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Stalking was also identified as a common component of IPV that is more prevalent in sexual minority relationships than in heterosexual relationships. Studies largely recruit heterosexual samples and seldom take stock of sexual minority populations (Chen et al, 2020; Langenderfer-Magruder et al, 2020; Sheridan et al, 2019; Strand & McEwan, 2011), resulting in a scarcity of empirical data in the stalking literature base to expand the issue to gay and bisexual men (Black et al, 2011; Pathé et al, 2000). While many IPV studies exclude experiences of stalking, one study that examined both phenomena indicated that 66.27% of gay men and 60.38% of bisexual men reported victimization of intimate stalking as a form of IPV ( N =136; Dickerson-Amaya & Coston, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the sexual orientation of the victims was unavailable in most reports; further research on a wider sample should address the police forces to investigate the issue and the characteristics of the campaigns targeted to specific gender orientations. This could also help understand the role of acquaintances and strangers when stalking is related to sexual orientation [43]. Third, we were only allowed by the police forces to log into their files when they were classified as stalking (art.…”
Section: Limitationsmentioning
confidence: 99%